A new species of northeastern Brazilian endemic genus Harpochilus (Acanthaceae) - Monteiro, Fernanda Kalina Da Silva; Fernando, Emanoel Messias Pereira; Lucena, Maria De Fátima De Araújo; Miranda De Melo, José Iranildo (Phytotaxa, 2018)
A new species, Harpochilus paraibanus (Acanthaceae), is described from the semiarid region of Paraiba State, Brazil. The species is characterized mainly by having cylindrical branches and pale yellow corollas. Only nine individuals of this new species were encountered in the study area, resulting in its classification as endangered (EN) according to IUCN criteria.